2007
DOI: 10.1016/j.trstmh.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Screening for tuberculosis among 2381 household contacts of sputum-smear-positive cases in The Gambia

Abstract: Contact investigation is a key component of tuberculosis (TB) control in developed, but not developing, countries. We aimed to measure the prevalence of TB among household contacts of sputum-smear-positive TB cases in The Gambia and to assess the sensitivity of an enzyme-linked immunospot (ELISPOT) assay in this regard. Household contacts of adult smear-positive TB patients were assessed by questionnaire, purified protein derivative (PPD) skin test, ELISPOT assay, physical examination, chest X-ray and sputum/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…21 In settings using passive case detection, more TB cases are male than female; the male to female ratio is more evenly balanced when active case detection is used. 22 It should be noted that around 60% of study samples from Tongatapu were from males, whereas just over 50% of sputum samples were from males in the outer islands. This may be a chance finding, but requires further …”
Section: Discussionmentioning
confidence: 98%
“…21 In settings using passive case detection, more TB cases are male than female; the male to female ratio is more evenly balanced when active case detection is used. 22 It should be noted that around 60% of study samples from Tongatapu were from males, whereas just over 50% of sputum samples were from males in the outer islands. This may be a chance finding, but requires further …”
Section: Discussionmentioning
confidence: 98%
“…They found that the patients were less advanced than those found through passive case detection. [15] In Hong Kong, China, the household contact survey was also followed-up and considered to be a useful method in the detection of TB patients. [16] In our study, the index patients were not divided into MB and PB for analysis because the MB patients accounted for 87.9% of all newly detected patients in China.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Studies done in child contacts in African communities have shown that one-third to two-thirds of child household contacts of TB cases have evidence of TB infection (ie, TST-positive) [12,13]. Of children with TB, 70% to 80% have the disease in their lungs (pulmonary TB, PTB).…”
Section: Key Pointsmentioning
confidence: 99%